MIMO UWB Communications Using Modified Hermite Pulses - Abou-Rjeily, Chadi (2017)
In this paper, we present a new full rate scheme for exploiting diversity in multi-antenna ultra-wideband (UWB) systems. The independent data streams that are transmitted simultaneously from the different antennas are rendered orthogonal by the use of modified Hermite pulses. At a second time, appropriate real rotations enhance the transmit diversity level. We also consider, for the first time, the problem of maximum likelihood (ML) detection with multi-dimensional PPM and hybrid PPM-PAM constellations that can be used in conjunction with the proposed scheme